The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.14814/phy2.12652
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke represses the innate immune response to asbestos

Abstract: Both cigarette smoke (CS) and asbestos cause lung inflammation and lung cancer, and at high asbestos exposure levels, populations exposed to both of these carcinogens display a synergistic increase in the development of lung cancer. The mechanisms through which these two toxic agents interact to promote lung tumorigenesis are poorly understood. Here, we begin to dissect the inflammatory signals induced by asbestos in combination with CS using a rodent inhalation model and in vitro cell culture. Wild‐type C57BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…A very recent study in a mouse inhalation model shows that exposure to combined tobacco smoke and chrysotile asbestos suppressed the innate immune response (NLRP3 inflammasome) to asbestos fibers, resulting in reduced fiber clearance and more chronic inflammation, leading to carcinogenesis. Confirmatory in vitro studies in human monocytes produced a similar effect with combined tobacco smoke and asbestos exposure [98].…”
Section: The Synergy Between Asbestos Fibers and Tobacco Smoke For Lung Cancer Causation-animal Studiesmentioning
confidence: 64%
“…A very recent study in a mouse inhalation model shows that exposure to combined tobacco smoke and chrysotile asbestos suppressed the innate immune response (NLRP3 inflammasome) to asbestos fibers, resulting in reduced fiber clearance and more chronic inflammation, leading to carcinogenesis. Confirmatory in vitro studies in human monocytes produced a similar effect with combined tobacco smoke and asbestos exposure [98].…”
Section: The Synergy Between Asbestos Fibers and Tobacco Smoke For Lung Cancer Causation-animal Studiesmentioning
confidence: 64%
“…Indeed, IL‐1 β has been shown to be a marker of COPD severity as individuals with COPD present higher levels of IL‐1 β in serum . In contrast, another study shows that cigarette smoke reduces the inflammatory response in mice treated with another NLRP3‐activating crystal: asbestos . Although contradictory, the reduction of the inflammatory response could be explained by the promotion of the proteasomal degradation of NLRP3 mediated by its ubiquitination …”
Section: The Inflammasome: a Well‐regulated Immune Platform Also Presmentioning
confidence: 99%
“…Nigericin is a NLRP3 inflammasome inducer and the NLRP3 inflammasome is most likely to be involved in inhaled airway challenges such as E-vapour. While inhibition of inflammasome activation by basic E-vapour has not been reported before, NLRP3 inflammasome inhibition by cigarette smoke has been described (Morris., 2015; Han., 2017; Ye., 2019); NLRP3 protein was reduced via ubiquitin mediated proteasomal processing in THP1 cells and C57BL/6 mice exposed to cigarettes smoke, and the NLRP3 inflammasome was supressed in reaction to Candida albicans in a rat model exposed to cigarette smoke. Indeed, Morris et al showed the NLRP3 inflammasomes response to asbestos was inhibited by cigarettes smoke, while we show here that nigericin fails to activate primed macrophages in the presence of basic E-vapour.…”
Section: Discussionmentioning
confidence: 96%